2017
DOI: 10.1136/heartasia-2017-010938
|View full text |Cite
|
Sign up to set email alerts
|

Trend in prevalence of coronary artery disease and risk factors over two decades in rural Punjab

Abstract: In a rural population of Punjab, the prevalence of several CAD risk factors like sedentary lifestyle, hypertension, diabetes, obesity and hypercholesterolaemia increased over 20 years. These changes in risk factors were associated with a modest increase in prevalence of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…In a recently published study from India, the prevalence of diabetes has increased to 9.7% from the past 4.7% in 1994. 17 This was similar to the US population. But in comparison, the Indian population in Kuwait showed a dangerously higher prevalence of 20.5%.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a recently published study from India, the prevalence of diabetes has increased to 9.7% from the past 4.7% in 1994. 17 This was similar to the US population. But in comparison, the Indian population in Kuwait showed a dangerously higher prevalence of 20.5%.…”
Section: Discussionsupporting
confidence: 73%
“…Like the Indians in Kuwait, a study from rural India showed the prevalence of hypertension as 26.5%. 17 Prevalence of diabetes in the US was reported to be 9.9% (males 13.6%, females 11.2%). 9 On the other hand, the Indian subjects in the Kuwait study showed the overall prevalence of diabetes as 20.5% (males 21.7%, females 13%, p<0.1), which is much higher than in the affluent country like USA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies showed that majority of the study participants were hypertensives. 4,7,15,18 In this study, majority of the cases and controls do not practice exercise regularly but no significant association was found with development of IHD. This is similar to study conducted by Mendagudali et al, Oommen et al at rural block of Vellore, Krishnan et al at rural block of Kerala and Dhungana et al at Sitapaila Village in Nepal.…”
Section: Discussioncontrasting
confidence: 62%
“…In present study significant association was found between diabetes and hypertension with Ischemic heart disease (p=0.002) which is similar to study done by others. 11,15 In this study risk of IHD was 5 times more among Diabetics compare to those with non diabetics. In contrast, other studies showed that majority of the study participants were hypertensives.…”
Section: Discussionmentioning
confidence: 55%
“…In the study by Goyal and colleagues, repeated surveys were conducted in the same rural Indian population in 1994 and 2014 focusing on coronary artery disease (CAD) and its risk factors 5. Among adults aged 30 years and older from three villages in Ludhiana district in Punjab, clinical measures of CAD, obesity, hypertension, diabetes, hypercholesterolaemia and smoking status were obtained.…”
mentioning
confidence: 99%